Effects of salinity on microbialite‐associated production in Great Salt Lake, Utah. Issue 3 (21st February 2019) - Lindsay, Melody R.; Johnston, Rachel E.; Baxter, Bonnie K.; Boyd, Eric S.
Abstract : Microbialites, organosedimentary carbonate structures, cover approximately 20% of the basin floor in the south arm of Great Salt Lake, which ranges from 12 to 15% salinity. Photosynthetic microbial mats associated with these benthic mounds contribute biomass that supports secondary production in the ecosystem, including that of the brine shrimp, Artemia franciscana . However, the effects of predicted increases in the salinity of the lake on the productivity and composition of these mats and on A. franciscana fecundity is not well documented. In the present study, we applied molecular and microcosm‐based approaches to investigate the effects of changing salinity on (1) the primary productivity, abundance, and composition of microbialite‐associated mats of GSL, and (2) the fecundity and survivability of the secondary consumer, A. franciscana . When compared to microcosms incubated closest to the in situ measured salinity of 15.6%, the abundance of 16S rRNA gene templates increased in microcosms with lower salinities and decreased in those with higher salinities following a 7‐week incubation period. The abundance of 16S rRNA gene sequences affiliated with dominant primary producers, including the cyanobacterium Euhalothece and the diatom Navicula, increased in microcosms incubated at decreased salinity, but decreased in microcosms incubated at increased salinity. Increased salinity also decreased the rate of primary production in microcosm assays containing mats incubated for 7 weeks and decreased the number of A. franciscana cysts that hatched and survived. These results indicate that an increase in the salinity of GSL is likely to have a negative impact on the productivity of microbialite communities and the fecundity and survivability of A. franciscana . These observations suggest that a sustained increase in the salinity of GSL and the effects this has on primary and secondary production could have an upward and negative cascading effect on higher‐trophic‐level ecological compartments that depend on A. franciscana as a food source, including a number of species of migratory birds.